The Relationship Between Environmental Exposure and Genetic Architecture of the 2q33 Locus With Esophageal Cancer in South Africa - Matejcic, Marco; Mathew, Christopher G.; Parker, M. Iqbal (Frontiers in Genetics, 2019)
Oesophageal squamous cell carcinoma (OSCC) has a high prevalence in several countries in Africa and Asia. Previous genome-wide association studies in Chinese populations have identified several OSCC susceptibility loci, including variants on chromosome 2q33 and 6p21, but the contribution of these loci to risk in African populations is unknown. In this study we tested the association of ten genetic variants at these two risk loci on susceptibility to OSCC in two South African ethnic groups. Variants at 2q33 (rs3769823, rs10931936, rs13016963, rs7578456, rs2244438) and 6p21 (rs911178, rs3763338, rs2844695, rs17533090, rs1536501) were genotyped in a set of Black Xhosa (463 cases and 480 controls) and Mixed Ancestry (269 cases and 288 controls) individuals. Genotyping was performed using TaqMan allelic discrimination assays. The Pearson's chi-squared test was used to compare the allele frequency between cases and controls. Gene-environment interactions with tobacco smoking and alcohol consumption were investigated in a case-control analysis. A logistic regression analysis was further performed to elucidate the independent effect of each association signal on the risk of OSCC. The 2q33 variants rs10931936, rs7578456 and rs2244438 were marginally associated with higher risk of OSCC in the Mixed Ancestry population (ORs=1.39-1.58, p≤0.035), of which rs7578456 and rs2244438 remained significant after multiple correction (p<0.005). The associations with rs7578456 and rs2244438 were also observed across strata of tobacco smoking (ORs=1.47-2.75, p≤0.035) and alcohol consumption (ORs=1.45-2.06, p≤0.085) status. However, only the association with rs2244438, which lies within an exon of TRAK2, remained significant after adjustment for the other variants in the region. Interestingly, none of the variants tested were significantly associated with OSCC in the Black South African population. These finding implicate TRAK2 as a casual gene for OSCC risk in the Mixed Ancestry population of South Africa and confirm prior evidence of population-specific differences in the genetic contribution to OSCC, which may reflect differences in genetic architecture and environmental exposure across ethnic groups.